O trabalho pedagógico da educação física: em busca das múltiplas determinações - Calheiros, Vicente Cabrera (2018)
This thesis is the result of a research carried out in the Doctoral Degree Program in Education, which is included in the Post-Graduate Program in Education at the Federal University of Santa Maria, and linked to the School Practices and Education Public Policies Line of Research and Kairós Study and Research Group on Work, Public Policies and Education. The research aimed to analyze how the pedagogical work in Physical Education in public schools is organized and characterized given the process of reordering of the world of work. Hence, through the investigation performed from the viewpoint of historical-dialectical materialism, the historical development of the capitalist society formation was analyzed by taking work as the key concept of articulation. Thus, I approach the existing relations among the general components socially established for education, and specifically within schools, by pointing out developments in the pedagogical work. The study showed that the pedagogical work is organized through the capitalist labor process and is determined by the contradictions that occur in this movement. Therefore, since such work is related to the educational field, it is characterized as non-material.